Optimal Ratio Determination of Tembang Fish Meal Addition (Sardinella Fimbriata) in Biscuit Making Through Organoleptic Quality and Moisture Content Evaluation - Nurfadilah Nurfadilah; Reski Fitriah; Darsiani Darsiani; Dewi Yuniati; Safriyanto S. Maruka (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to determine the optimal ratio of tembang fish flour addition to enhance the nutritional value of biscuits while maintaining their quality. Methodology: The research was conducted from June to July 2022 at the Applied Marine Product Processing Technology Laboratory and the Basic Laboratory of Politeknik Palu, Central Sulawesi Province. A Completely Randomized Design (CRD) was used for moisture content tests, and a Randomized Block Design (RBD) was used for organoleptic tests with five treatments of tembang fish flour addition: P1 (0 g), P2 (10 g), P3 (15 g), P4 (20 g), and P5 (25 g), each repeated three times. Results: The study found that the best addition of tembang fish flour in biscuits was P4, with a preference level of 'Like' (score 4) and moisture content below the maximum standard for biscuits (3.5% per 100 grams). Findings: Tembang fish biscuits are economical and significantly cheaper than other brands. Novelty: This research explores the use of tembang fish flour to diversify and enhance the nutritional profile of biscuits. Originality: The study offers detailed analysis and evidence of the nutritional and economic benefits of adding tembang fish flour to biscuits. Conclusions: Adding tembang fish flour improves the nutritional value and quality of biscuits, making them a viable and economical alternative. Type of Paper: Empirical Research Article